Government fiscal policy impact analysis in infrastructure sector and education sector to improve public welfare - Mustafa Edwin Nasution; Imam Wahyudi (Universitas Islam Indonesia, 2017)
This study aimed to conduct a study and analysis of government fiscal policies related to the components of revenue (taxes) and some components of spending (education/human resources and infrastructure sectors). Issues regarding the effectiveness of the allocation of government budgets, particularly for human resources and infrastructure sectors, is an important issue that is very interesting to discuss. Especially if associated with their impact on improving people's welfare. With a limited income, the government must make a choice to prioritize the education/human resources sector or infrastructure sector.